Decelerating aging process with physical activity - a review - Uram, Ewa; Osuch, Magdalena; Bogacz, Rafał; Gaik, Magdalena; Magda, Inga; Gazda, Dawid (Journal of Education, Health and Sport, 2023)
Introduction: The process of aging is a progressive, patterned, and accumulative set of time-related changes resulting from a mix of genetic, epigenetic, and environmental factors, that are constantly evolving, and that lead the human body to be more prone to defects and susceptible to disease, and at last to death. On the molecular level, the accumulation of free radical reactions that constantly go on in every cell and tissue is thought to be the main culprit behind the process of aging [1]. These reactions amassed over time, hamper immune responses to external factors, cause homeostatic imbalance and lead to chronic pro-inflammatory status in body cells. This process has been dubbed “inflammaging” [2]. Physical activity, along with a balanced diet and a healthy lifestyle as a whole, has long been thought to be crucial in retaining health and good quality of life. Aim of the study: A review of current knowledge about the process of aging, a summary of underlying pathologies, and current preventive protocols, with a focus on physical activity as a preventative measure in combating illness and age-related pathologies. Methods and materials: A review of chosen literature in the PubMed database, MDPI database, and GoogleScholar was conducted using the following keywords: “aging pathophysiology”, “physical exercise in the aging process”, “aging process underlying conditions”, “molecular biology of aging”, “cell lifespan”, “cell longevity”. Results and conclusions: Physical activity helps decelerate the process of aging, both physical and cognitive, through various pathways in the human body.